2009
DOI: 10.1007/978-3-642-03315-5_18
|View full text |Cite
|
Sign up to set email alerts
|

Testing Privacy Awareness

Abstract: In web-based business processes the disclosure of personal data by the user is an essential part and mandatory for the processes. Privacy policies help to inform the user about his/her rights and to protect the user's privacy. In this paper we present a test to empirically measure how the user's privacy awareness changes by presenting specific elements of the privacy policy in close proximity to the required data items. We compare an experimental group using an enhanced interface to a control group using a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 13 publications
1
34
0
Order By: Relevance
“…We conducted a qualitative lab study to evaluate the effects of the privacy extensions on user's privacy awareness and concerns. Our goals were: (1) to understand users' baseline 4 http://www.alexa.com/topsites, list retrieved on July 1, 2014. privacy awareness and concerns during browsing without using an extension; (2) to learn how each extension influences privacy awareness and concern; and (3) to understand the impact of different user interface elements. Our study was approved by CMU's Institutional Review Board.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…We conducted a qualitative lab study to evaluate the effects of the privacy extensions on user's privacy awareness and concerns. Our goals were: (1) to understand users' baseline 4 http://www.alexa.com/topsites, list retrieved on July 1, 2014. privacy awareness and concerns during browsing without using an extension; (2) to learn how each extension influences privacy awareness and concern; and (3) to understand the impact of different user interface elements. Our study was approved by CMU's Institutional Review Board.…”
Section: Methodsmentioning
confidence: 99%
“…In the context of online tracking, privacy awareness entails an understanding about what data is being collected by which entities for what purposes, what entities that information is shared with, and corresponding risks and benefits [17]. Bergmann found that presenting specific elements of a privacy policy in close proximity to the required data positively impacts privacy awareness [4]. Malandrino et al found that people without a technical background were likely to take steps to protect their privacy when made privacy aware [11].…”
Section: A Privacy Concerns and Awarenessmentioning
confidence: 99%
See 2 more Smart Citations
“…INTRODUCTION Privacy can be defined as "the right of self-determination regarding data disclosure" [4]. Hence, individual privacy settings for online social networks determine what information a user discloses to others.…”
mentioning
confidence: 99%